2016
DOI: 10.1111/1475-6773.12537
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Readmissions among Heart Failure Patients Discharged to Home Health Care: Effectiveness of Early and Intensive Nursing Services and Early Physician Follow‐Up

Abstract: Our results call for closer coordination between home health and medical providers in the clinical management of HF patients immediately after hospital discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 34 publications
1
81
0
Order By: Relevance
“…If independently validated in other studies, these risk profiles could be used by primary care and other community-based clinicians to identify older adults living in the community who may be at risk for poor outcomes and trigger clinicians to initiate individualized, targeted interventions. Targeted interventions may include the initiation, continuation or increased frequency of several community-based services such as nurse-led care coordination, 34 home health care, 39,40 hospice, phone calls between visits, 41 telehealth, 42 physician follow up 43 and handyman services 44 to mitigate risk. Additionally, the risk profiles, if further refined, could be integrated into clinical decision support systems to assist clinicians identify specific community-based referrals needed by older adults according to their level of risk.…”
Section: Discussionmentioning
confidence: 99%
“…If independently validated in other studies, these risk profiles could be used by primary care and other community-based clinicians to identify older adults living in the community who may be at risk for poor outcomes and trigger clinicians to initiate individualized, targeted interventions. Targeted interventions may include the initiation, continuation or increased frequency of several community-based services such as nurse-led care coordination, 34 home health care, 39,40 hospice, phone calls between visits, 41 telehealth, 42 physician follow up 43 and handyman services 44 to mitigate risk. Additionally, the risk profiles, if further refined, could be integrated into clinical decision support systems to assist clinicians identify specific community-based referrals needed by older adults according to their level of risk.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another study of heart failure patients found that neither one week home health nor one week primary care visits were preventative of 30-day readmissions but, in combination, they significantly reduced the likelihood of hospital readmissions. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Some of the study participants described it as providing early, frequent visits, while others specified the number of visits, such as at least three times per week, or every other day, or even back-to-back visits. In a recent definition of frontloading, a panel of experts in HH and heart failure suggested a specific number and timing of nursing visits within the first posthospital week (Murtaugh et al, 2017). Their definition is broadly aligned with our findings and provides direction to visiting nurses as they develop visit plans.…”
Section: Discussionmentioning
confidence: 99%
“…Early and intensive skilled nursing visits contribute to decreased hospital readmission when combined with a physician follow-up visit in the first week after hospital discharge (Murtaugh et al, 2017). Nurses need to identify who would benefit from this treatment combination to prevent or at least delay hospital readmissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation